2010
DOI: 10.1021/es9028167
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Air Pollutants Emission Reduction during the 2008 Olympic Games in Beijing

Abstract: Air quality was a vital concern for the Beijing Olympic Games in 2008. To strictly control air pollutant emissions and ensure good air quality for the Games, Beijing municipal government announced an "Air Quality Guarantee Plan for the 29th Olympics in Beijing". In order to evaluate the effectiveness of the guarantee plan, this study analyzed the air pollutant emission reductions during the 29th Olympiad in Beijing. In June 2008, daily emissions of SO(2), NO(X), PM(10), and NMVOC in Beijing were 103.9 t, 428.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
176
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(178 citation statements)
references
References 32 publications
1
176
0
1
Order By: Relevance
“…It was noteworthy that, during the month of August in 2008, R value suddenly drops to much lower than what is expected during this time of year. This was likely due to the 2008 Beijing Olympics Games, during which several traffic and emission restrictions were strictly enforced from the period of April 2007 to January 2009, as has also been confirmed by Wang et al [49].…”
Section: Airrgb Trend Of Citiessupporting
confidence: 57%
“…It was noteworthy that, during the month of August in 2008, R value suddenly drops to much lower than what is expected during this time of year. This was likely due to the 2008 Beijing Olympics Games, during which several traffic and emission restrictions were strictly enforced from the period of April 2007 to January 2009, as has also been confirmed by Wang et al [49].…”
Section: Airrgb Trend Of Citiessupporting
confidence: 57%
“…As a result, the traffic volume and vehicular exhaust decreased significantly (Wang et al, 2010a;Zhou et al, 2010). For example, during the Olympic Games the traffic volume and average PM 2.5 concentration near a major road -about 1.2 km away from the TH site -reduced by 21 % and 46.3 % compared to those in June, respectively (Kong et al, 2010).…”
Section: Seasonal Patterns Of Carbonaceous Speciesmentioning
confidence: 99%
“…This led to additional measures to reduce emissions in targeted sectors in neighboring provinces of Tianjin, Hebei, Shanxi, Shandong, and Inner Mongolia, in order to assure good air quality for the Beijing Olympic Games. Consequently, surface and satellite measurements showed that the measures taken in Beijing and surrounding regions during the Olympic Summer Games likely had a noticeable effect on emission reduction and air quality improvement (Cermak and Knutti 2009;UNEP, 2009;Wang et al, 2010a, b). The emission control and large reduction in Beijing represents a human-perturbation experiment of unprecedented scale, and provides a rare opportunity to study the impact of pollution emissions on the air quality and atmospheric chemistry (Wang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that were not discussed in this paper may also contribute to overall air quality, including meteorological conditions (Barman et al, 2008;Cermak and Knutti, 2009;Wang et al, 2009;Ren et al, 2011), topographical influences, emission sources (Wang et al, 2010), transport from the stratosphere and long-range transport (Zhao et al, 2010a). Further examination of all these variables could improve ability to predict variance in air quality.…”
Section: Tablementioning
confidence: 96%